2021
DOI: 10.3390/chemengineering5010001
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Benzalkonium Chloride Based Antibacterial Paper for Health and Food Applications

Abstract: Pathogenic bacteria and other microorganisms pose a potent threat to humans by causing various infectious diseases. To control the spread of infection, different antibacterial products have been developed. However, most of them are known to be associated with health hazards, environmental pollution, complex fabrication, and/or higher cost. To address these issues, in this study, a low cost, biodegradable and human skin compatible antibacterial paper has been developed. A quaternary ammonium compound, benzalkon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The current study showed that hand wiping with alcohol-free hand sanitizer wipes was less efficacy than handwashing with water and plain soap and hand rubbing with alcohol sanitizer in reducing isolated bacteria of the hand, and this difference was statistically significant (P<0.05), this result is consistent with Sickbert et al study [26]. Although BAC was approved as an antimicrobial in many studies [25,27], this effect extremely depends on the proper preparation with proper concentration, which is maybe not achieved in many hand wipes industries. The current studyto our knowledge-is the first one in Kurdistan-Iraq that evaluates the efficacy of hand wet wipes as an antiseptic agent, but it was limited to the antibacterial effect, further studies include the antiviral and antifungal activity should be conducted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study showed that hand wiping with alcohol-free hand sanitizer wipes was less efficacy than handwashing with water and plain soap and hand rubbing with alcohol sanitizer in reducing isolated bacteria of the hand, and this difference was statistically significant (P<0.05), this result is consistent with Sickbert et al study [26]. Although BAC was approved as an antimicrobial in many studies [25,27], this effect extremely depends on the proper preparation with proper concentration, which is maybe not achieved in many hand wipes industries. The current studyto our knowledge-is the first one in Kurdistan-Iraq that evaluates the efficacy of hand wet wipes as an antiseptic agent, but it was limited to the antibacterial effect, further studies include the antiviral and antifungal activity should be conducted.…”
Section: Discussionsupporting
confidence: 90%
“…The United States Food and Drug Administration (US FDA) classified BAC as a category III antiseptic ingredient for the lack of sufficient safety data [24]. The action of BAC depends on the concentration; it is used as a preservative by a concentration ranges from 0.004 to 0.01%, while the concentration of 0.15% is considered the optimum as antimicrobial [25]. The current study showed that hand wiping with alcohol-free hand sanitizer wipes was less efficacy than handwashing with water and plain soap and hand rubbing with alcohol sanitizer in reducing isolated bacteria of the hand, and this difference was statistically significant (P<0.05), this result is consistent with Sickbert et al study [26].…”
Section: Discussionmentioning
confidence: 99%
“…The last assumption may be less probable since no difference in the effect of either (−)-myrtenol or (+)-myrtenol on the S. aureus membrane could be observed ( Figure 2 ). Nevertheless, the mechanism of both (−)-myrtenol and (+)-myrtenol synergy with conventional drugs is apparently driven by membrane damage since the treatment with both terpenes led to a drop in membrane potential similar to the action of benzalkonium chloride ( Figure 2 and Figure 3 ), the membrane-permeating agent [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%